The Role of Non-Verbal Interaction in a Short-Term Psychotherapy: Preliminary Analysis and Assessment of Paralinguistic Aspects - Diego Rocco (Research in Psychotherapy, 2013)
Analysis at a paralinguistic level of communication, already conceptualized within the multiple code theory, would appear to be very important in order to fully describe the quality of the patient-therapist relationship. In this study the therapeutic process and microprocess are analyzed taking into consideration a specific paraverbal aspect (speech rate) present in patient and therapist's communication. More specifically, in this paper we aim to investigate the relationship between the speech rate of both patient and therapist with the linguistic aspects of their referential process as obtained by the IDAAP dictionaries, relating to three sessions belonging to different phases of the psychotherapy. The results show that there are many significant correlations between the considered values. These findings are interpreted as an expression of the alignment between patient and therapist which can be linked to the outcome of the psychotherapy.